The distinctive place of induction in education - Fitz, Jessie Lois (My University, 1904)
Introduction: Induction as used in this instance refers to that process of reasoning in which the observation of individual or particular instances and the inferences drawn from these observations to form generalizations is the method followed. By its place in education is meant the part induction plays in the passage from old knowledge to the new or from individual truths to general laws. Active knowledge getting is the idea convoyed by the word education and not accidental information which comes without one’s personal effort. This method of instruction is one of peculiar interest and importance to all who are engaged in assisting young persons in acquiring an education and forming correct mental habits. It even holds an important place in every day life because it treats instances of common experience in an analytical manner.
Citation: Fitz, Jessie Lois. The distinctive place of induction in education. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Education; Induction; Philosophy; History of Reasoning; Theses; Manuscripts (documents)